Potential Elevation Shift of the European Beech Stands (Fagus sylvatica L.) in Serbia - Lazar Pavlović; Dejan Stojanović; Emina Mladenović; Milena Lakićević; Saša Orlović; Saša Orlović (Frontiers in Plant Science, 2019)
According to climate projection models, the global temperature is expected to rise by at least 1.5°C by the end of this century. According to some studies the expected rise in Serbia is even higher. Global warming may result in creating new areas for forest growth. Although creating new forests would be a positive outcome in some areas, global warming can cause negative impacts in other areas, and this can lead to forest loss and the shift of geographical ranges, or even extinction, of plant species. The European beech is the dominant forest tree species in Serbia, featuring high ecological importance and economic value. In mixed or pure stands, beech forests cover approximately 660,400 ha, accounting for 29.3% of the total Serbian forest area. In the present study, the effects of climate change on the distribution of the European beech stands in Serbia, with an emphasis on their elevation shifts, were examined using species distribution models (SDMs). Data for the present tree cover in Serbia, climate projections, and environmental data were used for model building. The models were first tested against present inventory data. In these tests, the models were found to provide accurate projections, as shown by their true skills statistics (TSS) values ranging from 0.652 to 0.736 and area under the curve (AUC) values ranging from 0.868 to 0.937. The potential distribution patterns predicted by the models indicate that the European beech elevational distribution in Serbia would decrease, exhibiting a significant upward shift in elevation during the first part of this century. Current beech stand locations could be changed, and other areas at higher elevations may be more suitable for beech growth. After 2071, European beech stands at elevations below 500 m would be even smaller. This change is caused by temperature rise and occurrence of climate extremes. However, on the highest elevations, further upward shift of the species is not expected.